2019
DOI: 10.1016/j.ijmedinf.2019.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Use of the FITT framework to understand patients’ experiences using a real-time medication monitoring pill bottle linked to a mobile-based HIV self-management app: A qualitative study

Abstract: Objective-The purpose of this work was to conduct an in-depth analysis to understand patients' experiences using a real-time medication monitoring pill bottle linked to an HIV self-management app. Methods-A descriptive qualitative study design was used. In-depth interviews were conducted using a semi-structured interview guide at the 3-month follow-up visit during a trial of the app for improving medication adherence which began in January 2018. Eligibility criteria were HIVpositive, over the age of 18, owners… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 59 publications
0
34
0
Order By: Relevance
“…Similarly, the weCare team, which has done non-HIV work on social media, is currently developing a tailored Facebook, text, and social and sexual networking app–based intervention to help engage care [ 90 ]. Hwayoung et al [ 91 ] combined an electronic pill bottle, fitness tracker, and phone alerts and found that the pill bottle encouraged adherence and self-management of medications. However, they mentioned that the smart pill bottle was too small to fit all the pills, although they liked how it was easy to open and discrete [ 91 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the weCare team, which has done non-HIV work on social media, is currently developing a tailored Facebook, text, and social and sexual networking app–based intervention to help engage care [ 90 ]. Hwayoung et al [ 91 ] combined an electronic pill bottle, fitness tracker, and phone alerts and found that the pill bottle encouraged adherence and self-management of medications. However, they mentioned that the smart pill bottle was too small to fit all the pills, although they liked how it was easy to open and discrete [ 91 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hwayoung et al [ 91 ] combined an electronic pill bottle, fitness tracker, and phone alerts and found that the pill bottle encouraged adherence and self-management of medications. However, they mentioned that the smart pill bottle was too small to fit all the pills, although they liked how it was easy to open and discrete [ 91 ].…”
Section: Resultsmentioning
confidence: 99%
“…We applied the Fit between Individuals, Task, and Technology (FITT) framework developed by Ammenwerth et al [ 17 ], as it helps analyze the factors that influence the success or failure of information technology (IT) implementation in a health care setting. The FITT framework has already been shown to be useful in several case studies [ 18 - 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Women who were able to do so regarded the standalone character of e-Health as an opportunity to manage their own treatment. Self-efficacy as a requirement for the adoption of a digital intervention was also shown by Cho et al, who applied the FITT framework to study an app for medication adherence in HIV patients and found that participants with a strong belief in their ability to improve their general physical health were motivated to use the app [ 31 ]. Self-efficacy is not a total new concept in the field of urogynecology research as studies with regular, non-digital, PFMT have shown that it is a known predictor for adherence to PFMT [ 32 34 ].…”
Section: Discussionmentioning
confidence: 98%
“…Secondly, women found the use of reminder e-mails encouraging to adhere to PFMT, but they would prefer to set their own reminders, which would be facilitated more easily by a mobile app than by a website. Other studies also showed that it is important to set reminders yourself, creating the possibility to engage with the intervention [ 19 , 31 ].…”
Section: Discussionmentioning
confidence: 99%